Precariousness and the search for freedom in an urban center in southeastern Brazil in the 19th century - Caio da Silva Batista (Sankofa (São Paulo), 2020)
This article seeks to develop research on the precariousness of freedom and the struggle for freedom through the judicial system in Brazil during the second half of the 19th century. Against the background of the city of Juiz de Fora, in Minas Gerais province, this study aims to understand how slaves, free and freed, sought justice to prove or achieve the right to freedom. In addition to this aspect, it will be possible to analyze the everyday life of slaves, freed and free poor people in the urban slave society of 19th century Brazil.